Bibliometric analysis of shooting skills research: mapping trends and emerging topics in sports science - Ramadhan, Agung; Apriani, Leni (Indonesian Journal of Sport Management, 2024)
Shooting skills are an important aspect in various disciplines, including sports, and have attracted widespread attention from academic circles. This study aims to map emerging trends and topics in shooting skill studies over the past four decades using a bibliometric analysis approach. A total of 132 documents indexed in Scopus were analyzed using software such as VOSviewer and RStudio to evaluate publication trends, author contributions, institutional affiliations, country of origin, and frequently used keywords. The results show a significant increase in the number of publications after 2010, with a peak in 2023, reflecting the increasing academic interest in this topic. Authors such as Benton and Kingsley, as well as countries such as China, Indonesia, and the United States, stand out as major contributors. Thematic analysis identified key themes related to motor skills such as stability, accuracy, and agility, while recent trends focus on the use of advanced technologies such as virtual reality. The study also highlights the importance of international collaboration in advancing studies in this field. In conclusion, the integration of technology and interdisciplinary approaches offers great opportunities for developing shooting skill research in the future. These findings provide important contributions to understanding the development of literature in the field of sports science and open new directions for further research.